Comparison of the influence of photodynamic reaction on the Me45 and MEWO cell lines in vitro - Choromańska, Anna; Saczko, Jolanta; Kulbacka, Julita; Kamińska, Iwona; Skołucka, Nina; Majkowski, Michał (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study: Photodynamic therapy (PDT) is an approved, minimally invasive and highly selective therapeutic approach to a variety of tumors. It is based on specific photosensitizer accumulation in the tumor tissue, followed by irradiation with visible light. The photochemical interactions of the photosensitizer, light and molecular oxygen produce singlet oxygen and other reactive oxygen forms. The imbalance between ROS generation and antioxidant capacity of the body gives rise to oxidative stress in the cell, which initiates cell death in PDT. The aim of this study was to investigate the effect of photodynamic reactions in human melanoma cell lines. Material and methods: Photofrin® (Ph) was used for the photodynamic reaction in vitro as a photosensitizer. The primary cell line was MEWO cell line (granular fibroblasts), derived from a human melanoma. As a recurrent cell line we used Me45 cell line, derived from a lymph node metastasis of skin melanoma. We compared cell viability (MTT assay) to determine the effectiveness of applied therapy. The intracellular distribution of photosensitizer (Photofrin) and localization of mitochondria (Mito-Tracker Green) were detected by confocal microscopy. Results: We observed that Me45 and MEWO cell viability was dependent on the time of incubation after irradiation. In the recurrent cell line Ph accumulated mainly in the mitochondrial membranes and in MEWO cells also in the cytoplasm. The primary melanoma cell line exhibited significantly reduced cellular proliferation (below 50%) after photodynamic reaction with Ph. Conclusions : The applied photodynamic reaction was more effective in primary melanoma cells. Additionally, mitochondrial localization of Ph can lead to disturbances of mitochondrial transmembrane potential and finally to release of apoptotic proteins.